Relationship of Physical Performance with Body Composition and Bone Mineral Density in Individuals over 60 Years of Age: A Systematic Review - Hyehyung Shin; Lynn B. Panton; Gareth R. Dutton; Jasminka Z. Ilich (Journal of Aging Research)
The purpose of this review was to examine the relationship between physical performance and body composition measurements, including fat/muscle mass and bone mineral density (BMD) in individuals ≥60 years of age. Various measurements used to assess body composition, BMD, and physical performance (PP) were discussed as well. Medline/PubMed, CINAHL, and SCIE were used to identify articles. After limiting the search for age and kind of physical performance measures, 33 articles were evaluated. Higher fat mass was associated with poorer physical performance while higher muscle mass was a predictor of better physical performance, especially in the lower extremities. Additionally, evidence showed that higher muscle fat infiltration was a determinant of poorer physical performance. BMD was shown to be a good predictor of physical performance although the relationship was stronger in women than in men. Developing standardized methods for PP measurements could help in further investigation and conclusions of its relationship with body composition.